Changing Flow Paths Caused by Simultaneous Shearing and Fracturing Observed During Hydraulic Stimulation. Issue 3 (10th February 2020) - Krietsch, H.; Villiger, L.; Doetsch, J.; Gischig, V.; Evans, K. F.; Brixel, B.; Jalali, M. R.; Loew, S.; Giardini, D.; Amann, F.
Abstract: We monitored the seismohydromechanical rock mass response to high‐pressure fluid injection during a decameter‐scale hydraulic stimulation experiment in crystalline rock at the Grimsel Test Site, Switzerland. Time series recorded at two pressure monitoring locations show abrupt pressure increases that change in amplitude and appearance between subsequent stimulation cycles. Induced seismicity correlates with the propagation of one of these pressure fronts. Deformation data along the same shear zone shows permanent fracture dislocation preceded by strong transient fracture opening. We interpret these observations as nonlinear pressure diffusion along flow channels that reorganize in response to hydromechanical effects during stimulation. Combining these observations with the in situ stress field estimated before stimulation, we argue that the underlying hydromechanical processes involve mixed‐mode stimulation with both Mode I and II/III fracture dislocation. Plain Language Summary: Hydraulic shearing of preexisting fractures and hydraulic fracturing are commonly used to enhance the hydraulic conductivity and connectivity within in situ fracture networks, for example, in the framework of geothermal heat exploitation. Both treatments are based on high‐pressure fluid injections that induce deformation in the overall rock mass and dislocations along the fractures therein. It was previously observed that characteristic responses of both treatments can appear simultaneously during high‐pressure fluid injection. It is beneficial to locally resolve the different response behaviors in the rock mass, as they yield different connectivity enhancements. During a 20‐m‐scale stimulation experiment, we observed pressure signals within the target rock mass indicative of both shearing and fracturing behavior. These signals were monitored at 7 m distance to injection location. The aseismic/seismic character of these pressure signals is in agreement with the different response behavior. Including previously conducted in situ stress characterization data, we argue that our experiment provides insight into the simultaneous occurrence of shearing and fracturing behavior. The results of this study are important for the interpretation of reservoir‐scale stimulation experiments and predictive numerical modeling of rock mass responses to high‐pressure fluid injections. Key Points: Behavior of directly monitored high‐pressure pulses indicates nonlinear diffusion induced by fracture dilation High fracture fluid pressure signals change direction during stimulation and are associated with seismic and aseismic deformation Seismohydromechanical monitoring indicates a combination of Mode I and II/III deformation during high‐pressure fluid injections